Content accessibility in an institutional repository: analysis, tools and usage of the EPUB format - De Giusti, Marisa R. (2016)
The aim of this work is to describe alternatives introduced in EPUB 3 format to promote access to the academic and scientific institutional production by users with visual disabilities. The figure of the Institutional Repository is taken as starting line, understood as a space which hosts and disseminates this production, and whose objectives include maximizing its impact and fostering its visibility, both in the same line with the proposal of the study. Contributions in EPUB 3 format are analyzed and compared to its predecessors. Particularly, the existent extensions that are useful to optimize the voice synthesis for text to speech (TTS), the ability to add spare and multiple voices, and some of the available tools to visualize and reproduce TTS-enabled EPUB 3 documents. In this matter, the stress has been put on applications freely available for current mobile devices, in order to ensure that any potential user will be able to take advantage of these contributions. Lastly, the viability of implementing a circuit for accessible EPUB 3 documents generation is discussed, and further services for an institutional repository to offer from these tools are briefly mentioned.